Influência da transferência do ligamento coracoacromial no tratamento de lesões do ombro - Menegaz, Gabriela Lima (2014)
The upper limbs are constituted by the shoulder, arm, forearm and hand. The shoulder consists of the sternoclavicular, acromioclavicular and shoulder joints. The acromioclavicular joint is stabilized by ligaments and deltoid and trapezius muscles. The ligaments which constitute this joint are the acromioclavicular, coracoacromial and coracoclavicular, which is divided into trapezoid and conoid. The joint can be injured due to the direct fall on shoulder or on extended upper limb and are common in sports with hard contact. The acromioclavicular dislocation is classified into different types and there are specific treatments for each one. The Weaver-Dunn technique is one of the most common and consists in removing the intact coracoacromial ligament of the acromion, followed by its direct attachment to the structure of the clavicle. This technique has disadvantages when compared with others that do not require the transfer of the ligament. This occurs because it is an invasive procedure, require longer surgical time and require a longer period of healing. In this study, the techniques of Weaver-Dunn and coracoclavicular sling were evaluated. In both procedures, sutures are used to replace the coracoclavicular ligaments that have been injured. The analysis of the influence of coracoacromial ligament transfer was performed using three-dimensional models by the finite element method. Here is also investigated the tensile strength of some commercial sutures. Sutures composed by polyblend, as Fiberwire® and HiFi®, showed higher tensile strength than polyester sutures, as Ethibond®. In intact acromioclavicular joint, considering the proposed conditions, the trapezoid ligament showed higher stress values. The distance between the clavicle and the coracoid process showed similar behavior among the techniques evaluated. Thus, considering the simplifications of the models, it was concluded that there would not be a positive influence in the implementation of the transfer of the coracoacromial ligament to stabilize the acromioclavicular joint. To verify the results of this study, it is important the development of new numerical models and clinical research related to surgical techniques assessed.